Recent advanced development of metal-loaded mesoporous organosilicas as catalytic nanoreactors. Issue 24 (18th November 2021) - Liang, Yucang
Abstract : An up-to-date overview of the designability and catalytic application of transition metal-loaded mesoporous organosilica nanoreactors will be highlighted. Their synthetic approaches and catalytic performance are summarized. Abstract : Ordered periodic mesoporous organosilicas have been widely applied in adsorption/separation/sensor technologies and the fields of biomedicine/biotechnology as well as catalysis. Crucially, surface modification with functional groups and metal complexes or nanoparticle loading has ensured high efficacy and efficiency. This review will highlight the current state of design and catalytic application of transition metal-loaded mesoporous organosilica nanoreactors. It will outline prominent synthesis approaches for the grafting of metal complexes, metal salt adsorption and in situ preparation of metal nanoparticles, and summarize the catalytic performance of the resulting mesoporous organosilica hybrid materials. Finally, the potential prospects and challenges of metal-loaded mesoporous organosilica nanoreactors are addressed.